How Much Is Too Much Assessment? Insight into Assessment-Driven Student Learning Gains in Large-Scale Undergraduate Microbiology Courses - Jack T. H. Wang (American Society for Microbiology, 2013)
Designing and implementing assessment tasks in large-scale undergraduate science courses is a labor-intensive process subject to increasing scrutiny from students and quality assurance authorities alike. Recent pedagogical research has provided conceptual frameworks for teaching introductory undergraduate microbiology, but has yet to define best-practice assessment guidelines. This study assessed the applicability of Biggs’ theory of constructive alignment in designing consistent learning objectives, activities, and assessment items that aligned with the American Society for Microbiology’s concept-based microbiology curriculum in MICR2000, an introductory microbiology course offered at the University of Queensland, Australia. By improving the internal consistency in assessment criteria and increasing the number of assessment items explicitly aligned to the course learning objectives, the teaching team was able to efficiently provide adequate feedback on numerous assessment tasks throughout the semester, which contributed to improved student performance and learning gains. When comparing the constructively aligned 2011 offering of MICR2000 with its 2010 counterpart, students obtained higher marks in both coursework assignments and examinations as the semester progressed. Students also valued the additional feedback provided, as student rankings for course feedback provision increased in 2011 and assessment and feedback was identified as a key strength of MICR2000. By designing MICR2000 using constructive alignment and iterative assessment tasks that followed a common set of learning outcomes, the teaching team was able to effectively deliver detailed and timely feedback in a large introductory microbiology course. This study serves as a case study for how constructive alignment can be integrated into modern teaching practices for large-scale courses.